Prediction of the wheel profile wear using railroad vehicle dynamics simulation: Comparison of simulation and test results. (June 2018) - Feldmeier, Christofer; Li, Huaxia; Yamazaki, Yosuke; Kato, Takanori; Fujimoto, Takahiro; Kondo, Osamu; Sugiyama, Hiroyuki
Wear is a fundamental problem in the railroad vehicle design and performance evaluation. Slight changes in the profile shape result in significant impact on the contact geometry characteristics of wheel and rail, thereby altering the dynamic performance as well as derailment safety of railroad vehicles. In this study, a wear simulation capability integrated with multibody railroad vehicle dynamics simulation algorithms is developed considering multipoint contact exhibited between wheel and rail profiles in the wear evolution and validated against experimentally measured profiles obtained by the two-roller and scaled wheel wear tests. It was shown that worn profile shape as well as the magnitude of the weight loss agreed well between the simulation and test results in the two-roller test. Using wear test of a scaled wheel, it was found that the flange contact falls into severe wear regime, while the tread contact is in mild wear regime in the two-roller wear test data. However, a severe flange contact led to much higher wear rate than that obtained using the two-roller test for the same material and the same wear index, while the wear rate for the tread contact adhered to that of the two-roller test in the mild wear regime. This is attributed to the fact that contact condition of the severe flange contact scenario is greatly different from the two-roller contact condition due to the high contact pressure and slippage occurring in the small thin contact patch, leading to a vastly different wear rate per contact area. It is demonstrated that utilizing the flange wear rate leads to good agreement with the measured profile shape, while the two-roller wear rate leads to a significant underestimate of the flange wear due to significantly lower wear rate in severe wear regime.